Retrievable Filter Update: The Denali Vena Cava Filter - Hahn, David (Seminars in Interventional Radiology, 2015)
Over the past decade, there has been a gradual evolution of the retrievable inferior vena cava (IVC) filter, as the indications for caval filtration have expanded since the first such filters came into use. However, the particular design of retrievable or optional filters has introduced a subset of both symptomatic and asymptomatic device failures that have prompted a reassessment in the approach to patient selection as well as a new lexicon of technical considerations when considering retrieval. The Denali Vena Cava Filter (Bard Peripheral Vascular, Inc., Tempe, AZ) represents one of the latest filters to come to market that specifically addresses the various issues of its predecessors. While the body of published experience with this filter is still relatively sparse, the incidence of filter tilt, strut perforation, strut fracture, and filter migration appears acceptably low and the filters remain relatively easy to retrieve even after long dwell times.
Keywords: interventional radiology; IVC filter; retrievable IVC filter; filter tilt; strut perforation